Estradiol affects liver mitochondrial function in ovariectomized and tamoxifen-treated ovariectomized female rats - Moreira, Paula I. (2007)
Given the tremendous importance of mitochondria to basic cellular functions as well as the critical role of mitochondrial impairment in a vast number of disorders, a compelling question is whether 17[beta]-estradiol (E2) modulates mitochondrial function. To answer this question we exposed isolated liver mitochondria to E2. Three groups of rat females were used: control, ovariectomized and ovariectomized treated with tamoxifen. Tamoxifen has antiestrogenic effects in the breast tissue and is the standard endocrine treatment for women with breast cancer. However, under certain circumstances and in certain tissues, tamoxifen can also exert estrogenic agonist properties. We observed that at basal conditions, ovariectomy and tamoxifen treatment do not induce any statistical alteration in oxidative phosphorylation system and respiratory chain parameters. Furthermore, tamoxifen treatment increases the capacity of mitochondria to accumulate Ca2+ delaying the opening of the permeability transition pore. The presence of 25 [mu]M E2 impairs respiration and oxidative phosphorylation system these effects being similar in all groups of animals studied. Curiously, E2 protects against lipid peroxidation and increases the production of H2O2 in energized mitochondria of control females. Our results indicate that E2 has in general deleterious effects that lead to mitochondrial impairment. Since mitochondrial dysfunction is a triggering event of cell degeneration and death, the use of exogenous E2 must be carefully considered.